IMPLIKASI IMPLEMENTASI MODEL TPACK PADA PEMBELAJARAN IPAS DI SDN 109 PALEMBANG - Noer Faiza, Warda; Idris, Muhamad; Budi Irawan, David (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the Implications of the Implementation of the TPACK Model (Technological, Pedagogical, and Content Knowledge) in natural and social sciences at SDN 109 Palembang. The background of this research is the use of conventional teaching methods that cause student boredom, despite the availability of technological facilities that have not yet been utilized optimally. This study employs a descriptive qualitative approach with a case study strategy. The subjects of this study are the principal, class v c teachers and class v c students at SDN 109 Palembang. Data collection was carried out through observation, interviews and documentation. The data analysis technique used was the Miles and Huberman model, which encompasses data collection, data reduction, data display, and conclusion drawing. The results of the study show that the implementation of the TPACK model in natural and social sciences at SDN 109 Palembang has gone well because teachers in class v c are able to compile a teaching module that integrates the three main domains of TPACK and the implications of the implementation of the TPACK model have a positive impact on the learning process, including improving the quality of the learning process that is more contextual and meaningful, increasing student activity and participation in natural and social sciences materials as well as increasing interest and Motivation to learn. Nevertheless, several challenges remain to be addressed, namely the limited number of projectors that are sometimes shared between classes, electrical disruptions, and limited internet data quotas that can hinder the smooth running of technology-based learning. Therefore, continuous support from the school and relevant policy stakeholders is greatly needed to optimize the implementation of the TPACK model in natural and social sciences going forward. Keywords: Teaching models, TPACK models, Natural and Social Sciences.